2009
DOI: 10.1200/jco.2009.22.4659
|View full text |Cite
|
Sign up to set email alerts
|

Low Initial Human Papilloma Viral Load Implicates Worse Prognosis in Patients With Uterine Cervical Cancer Treated With Radiotherapy

Abstract: Our data suggest that HPV viral load is a strong independent prognostic factor for DFS. HPV type 18 showed a significant relationship with poor radiotherapy outcome in univariate analysis, but not in multivariate analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
54
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 17 publications
5
54
0
1
Order By: Relevance
“…Against this background, however, Kim et al reported that semi-quantitatively measured HPV DNA-load was a strong independent prognostic factor for disease-free survival of patients with cervical cancer treated with radical RT. 14 Thus, we aimed to analyze the impact of HPV16 DNA load on treatment outcomes in our series of anal SCC patients treated with standard CRT. In agreement with the findings by Kim et al, we showed that high HPV16 DNA load is an independent prognostic factor associated with improved locoregional tumor control and overall survival.…”
Section: Cancer Cell Biologymentioning
confidence: 99%
See 2 more Smart Citations
“…Against this background, however, Kim et al reported that semi-quantitatively measured HPV DNA-load was a strong independent prognostic factor for disease-free survival of patients with cervical cancer treated with radical RT. 14 Thus, we aimed to analyze the impact of HPV16 DNA load on treatment outcomes in our series of anal SCC patients treated with standard CRT. In agreement with the findings by Kim et al, we showed that high HPV16 DNA load is an independent prognostic factor associated with improved locoregional tumor control and overall survival.…”
Section: Cancer Cell Biologymentioning
confidence: 99%
“…In patients with cervical cancer, Kim et al recently reported that the semi-quantitatively measured HPV DNA load was a strong independent prognostic factor for diseasefree survival after radical RT. 14 The recent understanding of HPV infection as a causative factor in tumorigenesis, treatment response and prognosis …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In nasal NK/Tcell lymphoma, a low viral load of Epstein-Barr virus detected in formalin-fixed paraffin-embedded tissue was reported to be associated with better overall survival of the patients, compared to the high viral load (Hsieh et al, 2007). The prognostic value of HPV viral load has been evaluated in studies on HPV-associated cancers such as tonsillar squamous cell carcinoma and cervical carcinoma (Mellin et al, 2002;Datta et al, 2006;de Boer et al, 2007;Cohen et al, 2008;Kim et al, 2008Kim et al, : 2009Gnanamony et al, 2009;Kang et al, 2011). The studies on HPV16 DNA viral load detected in tissue samples (fresh frozen or paraffin-embedded) of tonsillar carcinoma demonstrated a significant association between low viral load and adverse prognosis (Mellin et al, 2002;Cohen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical significance Sumalee Siriaunkgul 1 , Utaiwan Utaipat 2 , Supaporn Suwiwat 3 , Jongkolnee Settakorn 1 , Kornkanok Sukpan 1 , Jatupol Srisomboon 4 , Surapan Khunamornpong 1 * of HPV viral load in patients with cervical carcinoma has been evaluated in only a small number of studies (Datta et al, 2006;De Boer et al, 2007;Kim et al, 2008Kim et al, : 2009Gnanamony et al, 2009;Kang et al, 2011). An association between a high HPV viral load in cervical carcinoma and a better prognosis has been described (Datta et al, 2006;Kim et al, 2009). To our knowledge, a study on HPV viral load in cervical NECA has not been reported.…”
Section: Introductionmentioning
confidence: 99%